Neuroendocrine-immune and metabolic accompaniments of cholecystokinetic effects of balneotherapy on SPA Truskavets’ - Marfiyan, O M; Korolyshyn, T A; Barylyak, L G; Kovbasnyuk, M M; Yavors’kyi, O V; Zukow, W; Popovych, I L (Journal of Education, Health and Sport, 2015)
Marfiyan O M, Korolyshyn T A, Barylyak L G, Kovbasnyuk M M, Yavors’kyi O V, Zukow W, Popovych I L. Neuroendocrine-immune and metabolic accompaniments of cholecystokinetic effects of balneotherapy on SPA Truskavets’. Journal of Education, Health and Sport. 2015;5(5):21-30. ISSN 2391-8306. DOI: 10.5281/zenodo.17307 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%285%29%3A21-30 https://pbn.nauka.gov.pl/works/556532 http://dx.doi.org/10.5281/zenodo.17307 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 – 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 15.02.2015. Revised 27.03.2015. Accepted: 15.04.2015. NEUROENDOCRINE-IMMUNE AND METABOLIC ACCOMPANIMENTS OF CHOLECYSTOKINETIC EFFECTS OF BALNEOTHERAPY ON SPA TRUSKAVETS’ O M Marfiyan1,2, T A Korolyshyn3, L G Barylyak1,3, M M Kovbasnyuk1,3, O V Yavors’kyi1, W Zukow4, I L Popovych1,3 1JSC “Truskavets’kurort”, Truskavets’, Ukraine olenka80@meta.ua 2Department of Pediatry, OO Bohomolets’ National Medical University, Kyiv, Ukraine 3Laboratory of Balneology, OO Bohomolets’ Institute of Physiology, Truskavets’-Kyiv, Ukraine i.popovych@ukr.net 4Faculty of Physical Education, Health and Tourism, Kazimierz Wielki University, Bydgoszcz, Poland w.zukow@ukw.edu.pl SUMMARY Objective. Ability balneofactors spa Truskavets’ (Ukraine), including bioactive water Naftussya, affect Gall-bladder motility has long been known. We set a goal to identify changes related neuroendocrine-immune complex and metabolism accompanying cholecystokinetic effect of balneotherapy on spa. Results. In observation of 22 men with chronic cholecystitis in combination with pyelonephritis, found that 10-12-day course of balneotherapy (drinking of bioactive water Naftussya, application of ozokerite, mineral baths) reduces Gall-bladder volume fasting by 16% (p< 0,001) and increases its contractile response to 40% solution of xylitol by 44% (p<0,001). This is accompanied by noticeable modulation of neuroendocrine-immune complex. In particular, decreases as the absolute and relative power spectral density (PSD) θ- and α-rhythms (p<0,05÷0,01) and increased relative PSD β-rhythm (p<0,05÷0,02) ongoing EEG. However, reduced heart rate variability indices: (VLF+LF)/HF by 34% (p<0,05) and LF/HF by 32% (p>0,05), by increasing PSD HF greater extent than LF. The basal levels of plasma cortisol decreased by 20% (p<0,01), testosterone by 15% (p=0,01), whereas increased levels of triiodothyronine (by 4%, p<0,05) and especially of calcitonin activity (92%, p<0,001)), calculated by urinary excretion of phosphates and calcium, which increases according by 103% (p<0,001) and 76% (p<0,01). It notes that higher urinary excretion of oxalates by 52% (p<0,001), creatinine by 32% (p<0,02), uric acid by 29% (p<0,001), urea by 21% (p<0,01), magnesium by 19% (p=0,05), with no significant changes in urinary excretion of chloride, potassium and sodium. This reduces the plasma level of creatinine by 14% (p<0,001) and urea by 11% (p<0,01). With respect to the parameters neutrophil phagocytic function stated increasing of index killing them Staphylococcus aureus by 19% (p<0,001) and Escherichia coli by 18% (p<0,01), coupled with a decrease in the number of microbes absorbed one phagocyte by 4% (p>0,2) and 8% (p<0,05) respectively. Regarding immunity parameters revealed significant increase in blood CD16+ lymphocytes only (+17%, p<0,01) in the absence of changes in levels of CD3+CD4+ and CD3+CD8+ T cells and CD19+ B lymphocytes. Do not change significantly either serum Igg G, M, A, or circulating immune complexes. Finally, stated a slight but significant increase electrokinetic index cell nuclei of buccal epithelium, indicating the "rejuvenation" of the body. Conclusion: balneotherapy on spa Truskavets’ be significantly cholecystokinetic effect, combined with the activation excretory and depurative kidney functions and neutrophil bactericidal function against a background of lower levels of neuroendocrine markers of stress. Keywords: Truskavets’, balneotherapy, cholekinetic, diuresis, neuroendocrine-immune complex.